2018
DOI: 10.1002/j.2617-1619.2018.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity interval training slows down tumor progression in mice bearing Lewis lung carcinoma

Abstract: Background We aimed to determine whether a short-term high-intensity interval training (HIIT) protocol could counteract tumor progression in an experimental model of lung cancer. Methods Mice were injected subcutaneously with Lewis Lung Carcinoma (LLC) cells and then randomly assigned into two groups: sedentary mice (LLC group) or mice submitted to HIIT (LLC + HIIT group). Results LLC + HIIT group had lower tumor mass than LLC group (-52% after 18 days), with no differences in glycolytic activity as measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Treadmill exercise for a period of 4 weeks, five times per week and 60 minutes each session, has demonstrated to significantly increase VEGF serum levels in mice inoculated with Lewis lung cancer (LLC) cells, as compared with baseline ( p = .015), but without significant differences in terms of survival rate or tumor growth compared with the control group . Alves et al observed 2.5‐fold higher mRNA levels of VEGF‐α ( p < .05) in an LLC mice model undergoing daily high‐intensity interval training after tumor cell injection compared with sedentary mice, with a significant reduction of tumor mass (−52% after 18 days) and benefit in survival .…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Treadmill exercise for a period of 4 weeks, five times per week and 60 minutes each session, has demonstrated to significantly increase VEGF serum levels in mice inoculated with Lewis lung cancer (LLC) cells, as compared with baseline ( p = .015), but without significant differences in terms of survival rate or tumor growth compared with the control group . Alves et al observed 2.5‐fold higher mRNA levels of VEGF‐α ( p < .05) in an LLC mice model undergoing daily high‐intensity interval training after tumor cell injection compared with sedentary mice, with a significant reduction of tumor mass (−52% after 18 days) and benefit in survival .…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…However, a minimum amount of exercise (2 km/day) is necessary to keep serum response factor levels elevated in cachexia over a threshold, which is necessary to exert beneficial effects. Serum response factor levels inversely correlate with wasting in mice, suggesting that serum response factor plays a role in maintaining body mass . Physical activity rescues serum response factor expression as well as its transcriptional activity, highlighting the importance of genetic activation induced by skeletal muscle activity for muscle rescue and homeostasis.…”
Section: Basic Sciencementioning
confidence: 99%
“…Not only triggers of muscle wasting were focused in the last years, but also the importance of exercise as treatment was analysed in many studies. Exercise counteracts cachexia, but it is unclear to which extent the exercise‐dependent mechanical stimulation of muscle per se plays a role in exercise beneficial effects . To study the mechanisms underlying mechanical stimulation, Coletti et al .…”
Section: Basic Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Such evidence is corroborated by studies that evaluate the rates of pro-inflammatory cytokines in animals with induced cancer undergoing exercise training. Interesting, High-Intensity Interval Training (HIIT) efficiently increases survival rate and reduces tumor mass growth in tumor-bearing mice ( Alves et al, 2018 ). Similar data can be found in a study that evaluated the effects of voluntary running against tumor progression and survival of animals with different tumor types.…”
Section: Exercise As Therapeutic Strategymentioning
confidence: 99%